UPAYA PEMBERDAYAAN WANITA MELALUI PROGRAM PELATIHAN TATA RIAS WAJAH - Rahma Afifah, Desti; Mulyanti, Kurniawati; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2024)
The community service programme aims to improve makeup skills among the people of Bojongmangu Village. The Bojongmangu Village community has beauty potential that can be developed. Therefore, through this community service activity, the author organised makeup training to improve the knowledge and makeup skills of the community, especially women, in caring for and beautifying their faces. The method of activity implementation includes practical demonstrations and participant training. In addition, this activity also provides practical guidance on how to apply good and correct make-up. The results of the community service activities can have a positive impact, in the form of increased self-confidence, job opportunities in the field of cosmetology, and increased community economy. The existence of this community service activity is expected that the field of makeup can provide tangible benefits to the people of Bojongmangu Village, providing real benefits for the community. Bojongmangu Village community, making a positive contribution to the development of local beauty, and open up new job opportunities in the field of cosmetology.